Phosphate and potash solubilizing bacteria from Moroccan phosphate mine showing antagonism to bacterial canker agent and inducing effective tomato growth promotion - Bouizgarne, B.; Bakki, M.; Boutasknit, A.; Banane, B.; El Ouarrat, H.; Ait El Maalem, S.; Amenzou, A.; Ghousmi, A.; Meddich, A. (Frontiers in Plant Science, 2023)
Most agricultural soils are facing limited phosphorus availability that challenges modern agriculture. Phosphate solubilizing microbia (PSM) has been explored extensively as potential biofertilizers for plant growth and nutrition, and harnessing phosphate rich areas could provide such beneficial microorganisms. Isolation of PSM from Moroccan rock phosphate led to the selection of two bacterial isolates, Bg22c and Bg32c, showing high solubilization potential. The two isolates were also tested for other in vitro PGPR effects and compared to a non-phosphate solubilizing bacterium Bg15d. In addition to phosphates, Bg22c and Bg32c were able to solubilize insoluble potassium and zinc forms (P, K, and Zn solubilizers) and produce indole-acetic acid (IAA). Mechanisms of solubilization involved production of organic acids as demonstrated by HPLC. In vitro, the isolates Bg22c and Bg15d were able to antagonize the phytopathogenic bacteria Clavibacter michiganensis subsp. michiganensis, causal agent of tomato bacterial canker disease. Phenotypic and molecular identification by 16S rDNA sequencing demonstrated delineation of Bg32c and Bg15d as members of the genus Pseudomonas and Bg22c as member of the genus Serratia. The two isolates Bg22c and Bg32c were further tested either alone or in a consortium and compared to the non-P, K, and Zn solubilizing Pseudomonas strain Bg15d for their efficacy to promote tomato growth and yield. They were also compared to treatment with a conventional NPK fertilizer. Under greenhouse conditions, Pseudomonas strain Bg32c remarkably improved the growth of whole plant height, root length, shoot and root weight, number of leaves and fruits, as well as fruit fresh weight. This strain also induced stomatal conductance enhancement. The strain also improved total soluble phenolic compounds, total sugars, protein, phosphorus and phenolic compounds contents compared to the negative control. All increases were more pronounced in plants inoculated with strain Bg32c in comparison with control and strain Bg15d. The strain Bg32c could be considered a potential candidate for formulation of a biofertilizer in order to improve tomato growth.